Penguatan Kepemimpinan Kepala Madrasah yang Efektif dalam Meningkatkan Kualitas Pendidikan - Arjiman, Arjiman (UAS PRESS, 2021)
This paper describes the strengthening of the educational leadership of madrasah principals in improving the quality of education. The context of leaders in educational institutions, must be distinguished from leaders in a company, considering that the products and approaches are different. Educational leaders have a focus on making educated people while company leaders have a focus on creating superior products. The object is people versus things. That's why being a leader of an educational institution is not only related to being able or not, competent or not, fulfilling the requirements or not but there must be a commitment that comes from the heart. Because what he wants to design is his heart and then his mind in developing Islamic educational institutions. This paradigm or perspective is not widely understood by some heads of Madrasahs in educational institutions so that it has an impact on the progress of Islamic educational institutions. Tulisan ini mendeskripsikan tentang penguatan kepemimpinan pendidikan kepala madrasah dalam meningkatkan kualitas pendidikan. Konteks pemimpin dalam lembaga pendidikan, harus dibedakan dengan pemimpin dalam suatu perusahaan, mengingat, produk dan pendakatannya berbeda. Pemimpin pendidikan memiliki fokus menjadikan manusia terdidik sementara pemimpin perusahaan memiliki fokus menciptakan produk unggulan. Obyeknya adalah manusia versus barang. Oleh sebab itulah manjadi pemimpin lembaga pendidikan tidak hanya berkaitan dengan bisa atau tidak, kompeten atau tidak, memenuhi syarat atau tidak tetapi harus ada komitmen yang bersumber dari hati. Karena yang hendak didesain adalah hatinya kemudian akalnya dalam mengembangakan lembaga pendidikan Islam. Paradigma atau cara pandang inilah yang tidak banyak difahami oleh sebagian kepala Madrasah di lembaga pendidikan sehingga berdampak terhadap kemajuan lembaga pendidikan Islam.